1997
DOI: 10.1103/physrevb.56.2852
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interface study on MBE-grownNd1.85Ce0.15CuO4

Abstract: Nd 1.85 Ce 0.15 CuO 4 ͑NCCO͒ surfaces and metal ͑Au, Ag, and Pb͒/NCCO interfaces have been extensively investigated by x-ray and ultraviolet photoelectron spectroscopies using films grown by molecular beam epitaxy ͑MBE͒. The photoelectron spectra obtained in situ on the surfaces of MBE-grown NCCO films are free from any dirt peak and show a fine structure with a Fermi edge in the valence region. Experiments were performed on the prepared clean surfaces, focusing on the evolution of the surface or interface ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…32 The O-1s spectrum of Nd 2 CuO 4 is depicted in Fig. 9 33 show a considerably larger FWHM of 3.39 eV ͑here 2.2 eV͒, results on polycrystalline samples are roughly in agreement with our results. 11,34,38 The intensity ratio between the satellite and main line for Nd 2 CuO 4 is also the smallest for all compounds studied here ͑see Table II͒.…”
Section: Theorysupporting
confidence: 89%
“…32 The O-1s spectrum of Nd 2 CuO 4 is depicted in Fig. 9 33 show a considerably larger FWHM of 3.39 eV ͑here 2.2 eV͒, results on polycrystalline samples are roughly in agreement with our results. 11,34,38 The intensity ratio between the satellite and main line for Nd 2 CuO 4 is also the smallest for all compounds studied here ͑see Table II͒.…”
Section: Theorysupporting
confidence: 89%
“…Similar studies are reported for Nd 2−x Ce x CuO 4 films in Ref. 23. The temperature dependence of dc resistivity of both films, as measured by the standard four probe method with evaporated Ag electrodes, is shown in Fig.…”
supporting
confidence: 85%
“…It should also be mentioned that although the partial oxygen pressure during "reduction" after the growth significantly affects the superconducting properties of the films, it affects the lattice constants very little, which we discuss elsewhere [11]. Figure 3 shows the variations of a 0 and c 0 in T'-La well known that, in T'-structure superconductors, the excess oxygen occupies apical sites and never leads to metallicity nor superconductivity [8,16,17]. With regard to the second possibility, the a 0 (x) curves of T'-La 2-x RE x CuO 4 as shown in Fig.…”
Section: Resultsmentioning
confidence: 93%